Building The Character of The Local Wisdom Perspective in The Press Industry - Diliyanti, Ni Nyoman; Sunariani, Ni Nyoman; Darmayanti, Ni Luh; Widnyani, Ni Made (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 15 Nomor 1 Tahun 2021, 2021)
Character is a mental or moral strength, that is the driving force, and differentiates it from other individuals. Character needs to be planted in the company to create human resources with character and ready to adapt well in order to development the company. Local wisdom can be used as an alternative in building the character of human resources (HR), because local wisdom is the noble values possessed by each region which are upheld by the values and meanings contained therein. Building character based on local wisdom will have a meaning when it is based on universal values ??that are rooted in the culture. One of the local wisdoms in Bali is the concept of Tri Kaya Parisudha. Tri Kaya Parisudha are three ethical teaching concepts that are controlled and harmonized, namely thoughts (manacika), words (wacika), and actions (kayika). Human character in the era of globalization should be assessed from the aspect of attitude or character, without prejudice to the numerical or numerical aspects of the assessment, seen as relevant as an indicator in building the character of human resources.